2002
DOI: 10.1046/j.1529-8817.2002.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

TROPHIC INTERACTIONS IN THE SEA: AN ECOLOGICAL ROLE FOR CLIMATE RELEVANT VOLATILES?1

Abstract: When attacked by herbivores, land plants can produce a variety of volatile compounds that attract carnivorous mutualists. Plants and carnivores can benefit from this symbiotic relationship, because the induced defensive interaction increases foraging success of the carnivores, while reducing the grazing pressure exerted by the herbivores on the plants. Here, we examine whether aquatic phytoplankton use volatile chemical cues in analogous tritrophic interactions. Marine algae produce several classes of biogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 100 publications
1
68
1
1
Order By: Relevance
“…DMSP is known to be made by a range of micro and macroalgae as well as by a few higher plants (Stefels, 2000), yet the functions of DMSP and its metabolites may be numerous and remain controversial. It has been suggested to function as an osmolyte , a cryoprotectant (Karsten et al, 1996), a grazing deterrent (Wolfe et al, 1997;Steinke et al, 2002), as a viral defence (Evans et al, 2006), and as an antioxidant (Sunda et al, 2002), amongst other roles. It should be noted that while phytoplankton are the main source of DMSP, recent advances in understanding the DMS cycle indicate that it is the entire marine planktonic food web that determines net DMS production along with photochemical and photobiological processes.…”
Section: Causes Of Seawater Dms Variabilitymentioning
confidence: 99%
“…DMSP is known to be made by a range of micro and macroalgae as well as by a few higher plants (Stefels, 2000), yet the functions of DMSP and its metabolites may be numerous and remain controversial. It has been suggested to function as an osmolyte , a cryoprotectant (Karsten et al, 1996), a grazing deterrent (Wolfe et al, 1997;Steinke et al, 2002), as a viral defence (Evans et al, 2006), and as an antioxidant (Sunda et al, 2002), amongst other roles. It should be noted that while phytoplankton are the main source of DMSP, recent advances in understanding the DMS cycle indicate that it is the entire marine planktonic food web that determines net DMS production along with photochemical and photobiological processes.…”
Section: Causes Of Seawater Dms Variabilitymentioning
confidence: 99%
“…Steinke et al (1998) reported that E. huxleyi CCMP 379 had nearly as high lyase activity as CCMP 373, yet this species was isolated in the English Channel where nutrients are relatively high and light penetration low. It is possible that certain phytoplankton maintain a high level of DLA in order to produce acrylate and DMS rapidly to deter grazing or to signal other organisms (Wolfe et al, 1997;Steinke et al, 2002c;Seymour et al, 2009). In addition, DMSP itself can deter grazing without the need for cleavage to the potentially toxic acrylic acid (Strom et al, 2003).…”
Section: Biological Roles Of Dlamentioning
confidence: 99%
“…There are different sources of specific variability in DMSP and DMSO production including growth stage, salinity, temperature, nutrient limitation and light related to several potential physiological functions of these molecules as osmoregulator (Vairavamurthy et al, 1985), cryoprotectant (Kirst et al, 1991), antioxidant (Sunda et al, 2002), methyl donor , grazing deterrent (Wolfe et al, 1997) and overflow mechanism in nitrogen-limiting conditions (Stefels, 2000). DMSP is also a source of carbon (C) and S for heterotrophic organisms (Kiene and Linn, 2000a) and acts as a chemical cue for higher trophic level organisms (Steinke et al, 2002). These physiological functions are not necessarily exclusive (Harada and Kiene, 2011) and phytoplankton cells may use several of them.…”
Section: Introductionmentioning
confidence: 99%